Risk management practices and their impact on the performance of Islamic banking institutions: A systematic literature review - Abdiriva, Budi; Yaya, Rizal (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to explore the role of risk management in enhancing the performance of Islamic banking institutions through a systematic literature review of 49 Scopus-indexed articles published between 2008 and 2023.Design/Methodology/Approach: Employing a structured review methodology, including bibliometric and thematic analysis using VOSviewer, the study categorizes existing literature into three key research clusters: banking regulation, bank management, and risk perception.Research findings: The findings reveal that risk management practices grounded in Sharia principles such as profit and loss sharing and equity financing, significantly influence Islamic banks’ financial performance and stability. Theoretical contribution/Originality: Theoretically, this review contributes to the body of knowledge by identifying 32 theories frequently employed in Islamic banking risk research, notably agency theory, signalling theory, and stakeholder governance.Practitioner/Policy implication: Practically, the study offers insights for policymakers to strengthen regulatory frameworks aligned with Islamic finance principles.Research limitation/Implication: Future research is encouraged to apply mixed-method approaches and further expand investigations into underexplored regions, such as Turkey, to contextualize risk management dynamics in Islamic banking environments.